Type-E hepatitis in rheumatoid arthritis patients. Issue 2 (3rd July 2017) - Kobayashi, Daisuke; Ito, Satoshi; Takai, Chinatsu; Abe, Asami; Ishikawa, Hajime; Murasawa, Akira; Narita, Ichiei; Nagoshi, Sumiko; Nakazono, Kiyoshi
Abstract: We experienced four cases of rheumatoid arthritis (RA) complicated with acute hepatitis caused by hepatitis E virus (HEV). All of them were asymptomatic, but they showed sudden deterioration of the liver function. No cases ate raw meat, including raw pork or deer. One case was using etanercept (ETN) with methotrexate (MTX). Two cases were using MTX but not biological disease-modifying antirheumatic drugs (bDMARDs). One case was not using either MTX or bDMARDs. When their liver dysfunction was revealed, MTX and ETN were discontinued. It was subsequently clarified that the subjects were infected with HEV. Liver dysfunction recovered in all cases, and MTX and ETN were restarted without any problems. When RA patients developed sudden-onset liver dysfunction, they might have been misdiagnosed with drug-induced liver injury. It is also possible that MTX, the anchor drug of the treatment of RA, would not be used any more if rheumatologists did not notice hepatitis E and misdiagnosed as MTX-induced liver injury. We should therefore check the HEV status, when RA patients show acute liver injury.